(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2010)
The present study ascertained how verbal contexts (instructions) and non-verbal contexts (objects) exert control over verbal responses in a total verbal episode. Participants consisted of 10 undergraduate students (19 to 26 years old). Four experimental conditions were employed by using subjects as their own control (within-subjects design). In the first three conditions, the instruction “Burn this tip now” was given, but in the second and third conditions, non-verbal stimuli were also shown. In the fourth condition, the instruction “Burn this tip now. Calm down, sir, or I will end up damaging your clothes” was given. For each condition, the participants were required to submit written answers. It was found that manipulated variables such as context controlled the participants’ verbal responses in each experimental condition. Explanations of contextual control took into consideration principles of discrimination, generalization and arbitrary conditional relations.